Effects of Community-Based Socio-Cultural Animation and Shade- Tree Theatre on Social Competence of Street Children in Oyo Town, Nigeria (2015)
The phenomenon of street children and the menace associated with it is assuming an alarming proportion especially in junction towns like Oyo, characterised by large-scale roadside activities. Although literature have established the importance of socio-cultural animation (SCA) and shade-tree theatre (STT) as effective intervention strategies to enhance the social competence skills of these children, available studies have only concentrated on other types of interventions such as value re-orientation, rehabilitation and job creation. Yet, the problem of street children persists. This study, therefore, determined the effects of community-based socio-cultural animation and shade-tree theatre on the social competence of street children in Oyo town, Nigeria. It further determined the moderating effects of gender and family size. The study employed a posttest only, control group, experimental design of 3x3x2 factorial matrix. Seventy-two consenting street children from intact and separated homes found on the street were selected through purposive sampling technique. Participants were randomly assigned to socio-cultural animation, shade-tree theatre and control groups. The treatment lasted ten weeks. Social Competence Skill Scale (r=0.83), socio-cultural animation, shade-tree theatre and placebo (control) activities guides were used for data collection. Three Focus Group Discussion sessions were also conducted with selected street children. Six research questions were answered and seven hypotheses tested at 0.05 significant level. Data were analysed using Analysis of Variance, Duncan post-hoc test and content analysis. Participants‟ mean age was 15.5 years, male 44.4% and female 55.5%. Majority (76.4%) were living with their parents with few (16.7%) from separated homes engaging in hawking, food fending, truck pushing and other services. Most of them (81.9%) were Oyo indigenes, 87.5% were in school and the remaining 12.5% were out of school. There was a significant main effect of treatment on street children‟s social competence (F (2, 55) = 3.34; 2 = 0.03). Children in the STT group had a higher adjusted posttest mean score in social competence ( ̅ = 71.18) than those in SCA group ( ̅ = 60.47) and control group ( ̅ = 59.85). Effect sizes for STT group (2 = 0.06) and SCA group (2 = 0.02) were six and two per cent respectively. There was no significant main effect of family size and gender on street children‟s social competence. The 2-way interaction effects of gender and family size and the 3-way interaction effects of treatment, gender and family size on street children social competence were not significant. Economic (poverty, unemployment) and non-economic (willingness, peer influence, pleasure seeking) were some of the factors responsible for children‟s street activities. The social competence of street children improved through participatory activities of shade-tree theatre and socio-cultural animation. However, the former was more effective than the latter. Regardless of gender and family size, the two participatory interventions should be adopted to enhance street children‟s social competence.